2016
DOI: 10.1371/journal.pone.0151965
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Persistent Cytomegalovirus Infection on Dynamic Changes in Human Immune System Profile

Abstract: Human cytomegalovirus (HCMV) imprints the immune system after primary infection, however its effect during chronic infection still needs to be deciphered. In this study we report the variation of blood cell count along with anti-HCMV IgG and T cell responses to pp-65 and IE-1 antigens, that occurred after an interval of five years in a cohort of 25 seropositive healthy adults. We found increased anti-viral IgG antibody responses and intracellular interferon-gamma secreting CD8+ T cell responses to pp-65: a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 34 publications
0
42
0
Order By: Relevance
“…IgG antibody inflation in MCMV infection was observed and high-dose infection was associated with the presence of neutralizing antibodies [106]. Importantly, an "inflationary" B cell response that gradually increases IgG levels to high frequencies was found in the persistent phase of HCMV infection [107]. This may indicate that CMV vectors may be exploited to induce not only an expanding T-cell response but also a life-long humoral immune protection against vectored antigens.…”
Section: Humoral Responsementioning
confidence: 96%
“…IgG antibody inflation in MCMV infection was observed and high-dose infection was associated with the presence of neutralizing antibodies [106]. Importantly, an "inflationary" B cell response that gradually increases IgG levels to high frequencies was found in the persistent phase of HCMV infection [107]. This may indicate that CMV vectors may be exploited to induce not only an expanding T-cell response but also a life-long humoral immune protection against vectored antigens.…”
Section: Humoral Responsementioning
confidence: 96%
“…The circulating T‐cell pool is characterized by the expansion of memory T cells after recovery from primary infection; significant differences persist between seronegative and seropositive subjects . Most memory T cells, particularly CD8 + T cells, monocytes as well as leucocytes, are increased in seropositive healthy adults after an interval of 5 years, whereas naive/precursor CD8 + T cells are decreased . CMV‐specific CD4 + and CD8 + T cells can also dominate the memory compartment of seropositive humans .…”
Section: Homeostasis Of and Selection Pressure On Cmv‐directed T Cellsmentioning
confidence: 99%
“…Furthermore, the effector‐memory T‐cell pool of CMV‐specific T cells varies among individuals and seems to correlate with the memory CD8 + T‐cell pool size . The opposing trends between two groups of individuals (CMV serostatus +/−) showed that the change of the CD4/CD8 ratio over time may be influenced by CMV infection; the former was significantly reduced in CMV‐seropositive individuals but it was increased in seronegative individuals …”
Section: Homeostasis Of and Selection Pressure On Cmv‐directed T Cellsmentioning
confidence: 99%
See 2 more Smart Citations